2009
DOI: 10.1111/j.1469-7610.2009.02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Refinement Strategy for detection of autism in 18‐month‐olds: a guarantee of higher sensitivity and specificity in the process of mass screening

Abstract: An extraction and refinement methodology utilizing child health surveillance programs achieve high efficacy for early detection of autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Other countries have adopted similar strategies, combining routine child-health surveillance with a standardised method. In Japan, the young autism and other developmental disorders checkup tool (YACHT) is administered by public health nurses to children aged 18 and 24 months 17. Wong and colleagues18 have modified the checklist for autism in toddlers (CHAT) for use in China, with a two-stage screening strategy in CHAT-23, incorporating a questionnaire and a direct observation stage that has more sensitivity and specificity than does CHAT.…”
Section: Clinical Characteristics and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Other countries have adopted similar strategies, combining routine child-health surveillance with a standardised method. In Japan, the young autism and other developmental disorders checkup tool (YACHT) is administered by public health nurses to children aged 18 and 24 months 17. Wong and colleagues18 have modified the checklist for autism in toddlers (CHAT) for use in China, with a two-stage screening strategy in CHAT-23, incorporating a questionnaire and a direct observation stage that has more sensitivity and specificity than does CHAT.…”
Section: Clinical Characteristics and Screeningmentioning
confidence: 99%
“…This assessment might be done through community resources (eg, early intervention staff, educators, psychologists, or speech pathologists), educational agencies, or local developmental clinicians. Reviews of early identification and screening are available 15,17,19. If concerns that a child has autism spectrum disorder are validated, comprehensive diagnostic assessment is needed (figure 1).…”
Section: Assessmentmentioning
confidence: 99%
“…M-CHAT and FYI), they did not calculate the estimated sensitivity for an unselected sample. Instead, they calculated sensitivity and specificity based on cases that were already diagnosed or included high-risk children, thereby increasing the prevalence of ASD (Honda et al, 2009) and thereby possible overestimation of the PPV and NPV. Other screeners that estimated the predictive validity based on a general population study yielded lower sensitivity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the prevalence of suspected ASD in our study (13.5%) was equivalent to the prevalence of suspected ASD among 18-month-old toddlers who were identified for follow-up in a previous study (i.e. 14.3%) [37], the assessment of suspected ASD is considered acceptable. Second, information on paternal characteristics such as age or occupation was not assessed, although previous studies reported that they might be independently associated with ASD [38], [39].…”
Section: Discussionmentioning
confidence: 40%